Pengaruh Penambahan Daun Kacang Tujuh Jurai (Phaseolus Lunatus, L) Fermentasi dalam Air Minum terhadap Performa Broiler.: The Effect of Adding Fermented Tujuh Jurai Bean Leaves (PhaseolusLunatus, L) to Drinking Water on Broiler Performance. - Farhan, Farhan; Debby syukriani; Fat, Nelzi; Nilawati; Malvin, Toni (Buletin Peternakan Tropis, 2025)
This study aimed to evaluate the effects of fermented kacang tujuh jurai (seven-branched peanut) leaf (DKTJF) supplementation in drinking water on the performance of broiler chickens, and to determine the most effective inclusion level. The leaves are known to contain various bioactive compounds, including alkaloids, terpenoids, flavonoids, steroids, saponins, phenolic compounds, and pheromones. The experiment was carried out over three months at the Nutrition and Feed Technology, Animal Production, Quality Testing, and Analysis Laboratories of the Payakumbuh State Agricultural Polytechnic. The materials used for preparing the treatment solution included 2 kg of fermented kacang tujuh jurai, 1 liter of EM4, 1 liter of molasses, and water. The materials used for broiler maintenance included day-old chicks (DOC), DKTJF, corn, soybean meal, minerals, coconut oil, fish meal, rice bran, and commercial feed. The equipment used for the treatment application included cages divided into 20 units (0.5 m × 0.5 m). A completely randomized design (CRD) was used, consisting of five treatment groups with four replications each, totaling 20 experimental units. Each unit contained four day-old chicks (DOC), resulting in a total of 80 broiler chickens. The treatments included DKTJF in the drinking water at 0%, 0.5%, 1%, 1.5%, and 2% levels. Observed parameters included body weight gain, feed intake, feed conversion ratio (FCR), water intake, and broiler performance index. The results showed that DKTJF supplementation significantly (P<0.05) affected body weight gain and water intake, but had no significant effect (P>0.05) on feed intake, FCR, or performance index. In conclusion, supplementation of up to 2% DKTJF in drinking water did not alter feed efficiency or overall performance, but it improved growth and reduced water consumption. The optimal inclusion level was identified at 1.5%.